2020
DOI: 10.1177/0301006620939457
|View full text |Cite
|
Sign up to set email alerts
|

A Continuous Illusion of Having a Sixth Finger

Abstract: Our body is central to our sense of self and personal identity, yet it can be manipulated in the laboratory in surprisingly easy ways. Several multisensory illusions have shown the flexibility of the mental representation of our bodies by inducing the illusion of owning an artificial body part or having a body part with altered features. Recently, new studies showed we can embody additional body parts such as a supernumerary finger. Newport et al. recently reported a novel six-finger illusion using conflicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 59 publications
0
21
1
Order By: Relevance
“…Guterstam et al (2011) took a different approach and demonstrated that even when the real right hand is fully visible and placed next to a right rubber hand, illusory ownership of the rubber hands can still be elicited while ownership of the real hand is maintained, thus eliciting an illusion of owning one extra right (rubber) hand. This latter paradigm has recently been extended to augmented reality with a virtual extra hand instead of a physical hand (Rosa et al, 2019; see also Newport et al [2016] and Cadete & Longo [2020] for subjective reports of an invisible extra little finger next to the real fingers in view in a mirror illusion). Collectively, the results presented in Ehrsson (2009) and Guterstam et al (2011) suggest that when the brain is presented with two right hands, both receiving congruent multisensory stimulation, both limbs are incorporated into the body representation and consciously experienced as one’s own.…”
mentioning
confidence: 99%
“…Guterstam et al (2011) took a different approach and demonstrated that even when the real right hand is fully visible and placed next to a right rubber hand, illusory ownership of the rubber hands can still be elicited while ownership of the real hand is maintained, thus eliciting an illusion of owning one extra right (rubber) hand. This latter paradigm has recently been extended to augmented reality with a virtual extra hand instead of a physical hand (Rosa et al, 2019; see also Newport et al [2016] and Cadete & Longo [2020] for subjective reports of an invisible extra little finger next to the real fingers in view in a mirror illusion). Collectively, the results presented in Ehrsson (2009) and Guterstam et al (2011) suggest that when the brain is presented with two right hands, both receiving congruent multisensory stimulation, both limbs are incorporated into the body representation and consciously experienced as one’s own.…”
mentioning
confidence: 99%
“…We recently replicated this effect and showed that by modifying the paradigm we could induce the percept of a stable sixth finger over an extended period of time (Cadete & Longo, 2020). By applying a continuous double stroking on the participant's fingers, followed by twenty double strokes on the "sixth finger" at the same time as the occluded little finger, we induced the illusion of having a sixth finger for a long duration, that is, throughout the twenty double strokes.…”
mentioning
confidence: 82%
“…In this regard, a series of pioneering studies [15], [21], [26], [42], [104] have explored various robotic SEs and their autonomous or movement/muscle based control as well as their application to augment movement. Basic related neuroscience aspects such as natural SE [2], multitasking, independence and coordination of SE and natural limbs [34], [51], learning [58], [105], SE embodiment [38], [40], and the feasibility of true DoF augmentation [36], have also been investigated, providing foundational knowledge of user capability for augmentation. The future promises of DoF augmentation may be illustrated by amazing prototypes developed in recent years some of which are shown in Fig.…”
Section: Towards Effective Human Movement Augmentationmentioning
confidence: 99%
“…Supernumerary fingers have taken the form of either an extra thumb [20], [22] or additional stabilising fingers [21]. Virtual SEs have been applied for studying a subject's ability to use an SE [34]- [37], or to better understand how subjects perceive augmentation through additional limbs [38]- [40] or fingers [41]. However, to date applications such as those in Fig.…”
Section: Introductionmentioning
confidence: 99%